Differential Detergent Extraction of Mycobacterium marinum Cell Envelope Proteins Identifies an Extensively Modified Threonine-Rich Outer Membrane Protein with Channel Activity - van der Woude, Aniek D. (American Society for Microbiology, 2013)
A striking characteristic of mycobacteria is the presence of an unusual outer membrane which forms a thick permeability barrier and provides resistance to many antibiotics. Although specialized proteins must reside in this layer, only few mycolate outer membrane (MOM) proteins have been identified to date. Their discovery is complicated by difficulties in obtaining good separation of mycobacterial inner and outer membranes. During our efforts to identify novel mycobacterial outer membrane proteins (MOMPs), we discovered that we can enrich for MOMPs using differential solubilization of mycobacterial cell envelopes. Subsequently, these different fractions were analyzed by nano liquid chromatography-tandem mass spectrometry (nanoLC-MS/MS). This proteomic analysis confirmed that our marker proteins for inner membrane and MOM were found in their expected fractions and revealed a few interesting candidate MOMPs. A number of these putative MOMPs were further analyzed for their expression and localization in the cell envelope. One identified MOMP, MMAR_0617 of Mycobacterium marinum, was purified and demonstrated to form a large oligomeric complex. Importantly, this protein showed a clear single-channel conductance of 0.8 ± 0.1 ns upon reconstitution into artificial planar lipid bilayers. The most surprising feature of MMAR_0617 is a long C-terminal threonine-rich domain with extensive modifications. In summary, we have identified a novel mycobacterial outer membrane porin with unusual properties.